PELATIHAN CHANOYU UPACARA MINUM TEH JEPANG UNTUK MENGGALI NILAI-NILAI BUDAYA SERTA MANFAAT YANG TERKANDUNG DI DALAMNYA - Rahmah, Yuliani; Widisuseno, Iriyanto; Wiyatasary, Reny; Mulyadi, Budi (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
Chanoyu is one of the most famous Japanese culture. Chanoyu is a traditional Japanese tea ceremony to honor the guests. This tea ceremony began in Japan in the Edo period. The most of Japanese learners knew that Chanoyu was just a tea ceremony which held to honor guests. They do not know about the culture values as well as the benefits and purposes of that tea ceremony.To know the cultural values, benefits and objectives of chanoyu ceremony, on October 14, 2017 Japanese Language Diploma Faculty of Humanities of Diponegoro University held a Community Service activity by inviting expert from The Japan Foundatioan Jakarta to practice and explain about the Chanoyu.The purpose of the Community Service devotion with the theme of chanoyu is that the Japanese language learners and the general public know more about the cultural values, benefits and objectives of the chanoyu ceremony.The result of this activity attains the knowledge of chanoyu which is not understood by Japanese language learners but by the public who interest of Japanese culture in general. With the knowledge of Chanoyu,we can understand about the philosophy in a cultural activity and the cultural values .